Exploring Polymeric Micelles for Improved Delivery of Anticancer Agents: Recent Developments in Preclinical Studies - Wei Fan; Yingzhe Wang; Chalet Tan (Pharmaceutics, 2013)
As versatile drug delivery systems, polymeric micelles have demonstrated particular strength in solubilizing hydrophobic anticancer drugs while eliminating the use of toxic organic solvents and surfactants. However, the true promise of polymeric micelles as drug carriers for cancer therapy resides in their potential ability to preferentially elevate drug exposure in the tumor and achieve enhanced anticancer efficacy, which still remains to be fully exploited. Here, we review various micellar constructs that exhibit the enhanced permeation and retention effect in the tumor, the targeting ligands that potentiate the anticancer efficacy of micellar drugs, and the polyplex micelle systems suitable for the delivery of plasmid DNA and small interference RNA. Together, these preclinical studies in animal models help us further explore polymeric micelles as emerging drug carriers for targeted cancer therapy.